New Euplocania species (Psocodea: Ptiloneuridae) from Colombia, Ecuador and Nicaragua, amendments and addition to species groups - González-Obando, Ranulfo; García-Aldrete, Alfonso; Carrejo-Gironza, Nancy; Vinasco-Mondragón, Andrés Felipe (Zootaxa, 2024)
Three new species of Euplocania (Ptiloneuridae) are described, illustrated, and assigned to two species groups. These new species are E. coyolarensis n. sp., E. erwini n. sp. and E. siona n. sp. The species group danubiana is re-diagnosed, by establishing that the male hypandrium is of one sclerite, rather than three, as it had been previously diagnosed. Among the amendments proposed, the species group zelayensis now includes only E. zelayensis García Aldrete and exclude E. reyesi García Aldrete, González Obando & Carrejo and E. guentherbuchi González Obando, García Aldrete & Carrejo, as had been previously established. Species group guentherbuchi is diagnosed and includes E. guentherbuchi and E. nasa González-Obando, García Aldrete & Carrejo. Euplocania coyolarensis n. sp., is described from Nicaragua, and includes as part of the species group danubiana. Species group D is also re-diagnosed and named group erwini, including the other two species described here.